Estimation of Iron(III) in Different Ores, Alloys and Medicinal Samples after its Separation with Adogen-464 - Chatterjee, A.; Basu, S. (Asian Journal of Chemistry, 2010)
Selective and quantitative extraction of iron(III) with 0.06(M) Adogen-464 (Methyl trialkyl(C8–C10) Ammonium chloride) in isoamyl alcohol from 6 M HCl medium and its subsequent determination by flame atomic absorption spectrophotometric method is described. Effects of different parameters like concentration of hydrochloric acid and amines, nature of diluents etc. have been studied. The method was applied successfully in the estimation of iron in several ores, minerals, alloys and medicinal samples.